Production, purification, crystallization and preliminary X-ray diffraction studies of the nucleoside diphosphate kinase b from Leishmania major - Costa Tonoli, Celisa Caldana; Vieira, Plinio Salmazo; Ward, Richard John; Arni, Raghuvir Krishnaswamy [UNESP]; Cavalcante de Oliveira, Arthur Henrique; Murakami, Mario Tyago (Wiley-Blackwell Publishing, Inc, 2009)
Nucleoside diphosphate kinases (NDKs; EC 2.7.4.6) play an essential role in the synthesis of nucleotides from intermediates in the salvage pathway in all parasitic trypanosomatids and their structural studies will be instrumental in shedding light on the biochemical machinery involved in the parasite life cycle and host-parasite interactions. In this work, NDKb from Leishmania major was overexpressed in Escherichia coli, purified to homogeneity and crystallized using the sitting-drop vapour-diffusion method. The NDK crystal diffracted to 2.2 angstrom resolution and belonged to the trigonal crystal system, with unit-cell parameters a = 114.2, c = 93.9 angstrom. Translation-function calculations yielded an unambiguous solution in the enantiomorphic space group P3(2)21.